Advanced detection for blu-ray disc optical recording - Lim, Melvin Heng Li. (2010)
The Blu-ray has come into its own and struck a chord in the hearts of the populace through its versatilities in high fidelity applications that entail exorbitance in both storage capacity and data rate. Despite having fallen on hard times, the prologue of the (1,7) Viterbi Detector, an amalgamation of the (1,7) Code and the Viterbi Algorithm, has engendered the renaissance of ultra-high density optical storage that was once nothing but a fantasy, and thus constitutes the raison d’être of this report. A litany of the essential components in a Blu-ray optical recording system that includes the (1,7) Code, the Blu-ray Partial Response Channel and the (1,7) Viterbi Detector, is recited to fathom the beauty of the Blu-ray. Likewise, MATLAB based simulation programs act as an acid test for the viability of superlative optical recording systems of the next generation. From the simulations, one of the several culminations elicited insinuates the potential of the (1,7) Code in reducing computational complexity as well as mitigating transmission impairments. Contrariwise, the connotation of the reciprocality of the user recording density to the performance of the (1,7) Viterbi Detector is a major stumbling block to the evolution of optical recording system. Therefore, the fate of the fourth generation optical recording system may innately lie on a breakthrough in a genre of Constrained Codes superior to that of the (1,7) Code.